Attitudes Towards Shared Learning of Trainee Dental Technicians and Undergraduate Dental Students. Issue 1 (1st January 2015) - Reeson, Michael G.; Walker‐Gleaves, Caroline; Ellis, Ian
Abstract : The challenges of health care are increasingly complex and subject to frequent change. Meeting these demands requires that health professionals work in partnership with each other and the patient. One way of contributing to this is for students to learn together. However, effective teamwork requires an education system that helps to foster understanding among all those entering the health workforce. The purpose of this study was to investigate the attitudes towards shared learning of undergraduate dental students and trainee dental technicians in a university dental school/hospital in the United Kingdom. Twenty‐five trainee dental technicians and 75 undergraduate dental students took part in the study over five academic years. Data were collected using structured questionnaires. A 100% response rate was achieved from the questionnaires. The results indicated the majority of students recognized the benefits of shared learning and viewed the acquisition of teamworking skills as useful for their future working lives, beneficial to the care of their patients, and likely to enhance professional working relationships. The study also found a positive association of being valued as an individual in the dental team by all student groups. Future dental curricula should provide opportunities to develop effective communication between these two groups and encourage teamworking opportunities. These opportunities need to be systematically developed in the dental curriculum to achieve the desired goals.